Biodegradable Mg alloys for orthopedic implants – A review - Violeta Tsakiris; Christu Tardei; Florentina Marilena Clicinschi (Journal of Magnesium and Alloys, 2021)
The last decade has seen a significant growth in the market for alloys used for implants, especially for those intended for orthopedic implants. Research into biodegradable magnesium-based alloys has made great strides in this period, so huge progress has been made in their use in the medical industry. The important factors that led to the intensification of research in this regard, were social but also economic, wanting to improve the quality of life, by reducing the use of conventionally permanent metallic implants (stainless steel, cobalt-based alloys, and titanium alloys) which involve the second implant removal surgery and other undesirable effects (stress shielding and metal ion releases), with a negative impact on the emotional and physical condition of patients, and by significantly reducing the costs for both the patient and the health system in the field of orthopedics. This paper refers to the impact and importance of biodegradable Mg alloys, reviewing the beginning of their development, the significant characteristics that make them so desirable for such applications (orthopedic implants) but also the characteristics that must be modulated (corrosion rate and mechanical properties) to arrive at the ideal product for the targeted application. It highlights, in detail, the mechanism and aspects related to the corrosion behaviour of Mg alloys, electrochemical characterization techniques / methods, as well as strategies to improve the corrosion behaviour and mechanical properties of these types of biodegradable alloys. The means of optimization, the category and the effect of the alloying elements, the design criteria, the requirements that the implants of biodegradable alloys Mg-based must meet and the aspects related to their efficiency are also presented. Finally, the potential applications in the specialized clinics, as well as the final products currently used and made by important prestigious companies in the world are approached.